Comment se repérer dans un monde problématique ? - Michel Fabre (Presses universitaires de la Méditerranée, 2011)
What means today finding a way in education? We shall analyze the transformations which affect henceforth the educational normativity and the double sliding which takes place from the imperative to the conditional way, without that it is still possible to take into account a principle of reality. In such a perspective, on what marks can indeed follows the educator? If we cannot follow the traditions or the Nature and if the idea of progress is not any more obvious, the last way is to think of experience in its absolute immanence, as pragmatism knew how to make it. If the education does not any more consist in following and in making follow quite drawn roads, it is necessary to invent new types of marks. That is why we suggest investigating the metaphors of the compass and the map. Maps and compass impose no road but help the traveller to find his way. With the compass, the educated draws its own road but with the help of experience already there, registered on the map.